2007
DOI: 10.4049/jimmunol.179.4.2477
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Role for the Bactericidal/Permeability Increasing Protein in Interactions of Gram-Negative Bacterial Outer Membrane Blebs with Dendritic Cells

Abstract: The bactericidal/permeability-increasing protein (BPI) is thought to play an important role in killing and clearance of Gram-negative bacteria and the neutralization of endotoxin. A possible role for BPI in clearance of cell-free endotoxin has also been suggested based on studies with purified endotoxin aggregates and blood monocytes. Because the interaction of BPI with cell-free endotoxin, during infection, occurs mainly in tissue and most likely in the form of shed bacterial outer membrane vesicles (“blebs”)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 58 publications
(47 reference statements)
3
44
0
Order By: Relevance
“…The C-terminal domain of BPI mediates the interaction of bacterial proteins with DCs (42). Based on our finding that anti-BPI IgG reactivity is specific to the CTBPI, we postulated that BPI cleavage might facilitate its delivery to the DCs in the context of NETosis and so lead to the breaking of tolerance.…”
Section: Resultsmentioning
confidence: 99%
“…The C-terminal domain of BPI mediates the interaction of bacterial proteins with DCs (42). Based on our finding that anti-BPI IgG reactivity is specific to the CTBPI, we postulated that BPI cleavage might facilitate its delivery to the DCs in the context of NETosis and so lead to the breaking of tolerance.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, bactericidal/permeability-increasing protein (BPI), but not LPS binding protein (LBP), enhanced the uptake of N. meningitidis vesicles (122). These interactions were surprisingly selective, since the same did not occur for macrophages, and BPI did not promote similar interactions of free lipooligosaccharide aggregates with the dendritic cells.…”
Section: Vesicle Entry Into Cellsmentioning
confidence: 97%
“…In a similar LPS binding study, Schultz et al investigated the role of BPI in binding Neisseria OM vesicle-derived LPS. Those authors observed that BPI binding of LPS was required for the OM vesicle interaction with dendritic cells, leading to CD14-mediated signaling and the expression of proinflammatory cytokines (122).…”
Section: Lps and Other Pampsmentioning
confidence: 99%
“…CD14 ϩ CD16 ϩ inflammatory monocytes are intrinsically involved in host defense, responding directly to invading pathogens through their transcription and release of multiple cytokines, promoting initiation of the acute phase response. In contrast, CD14 ϩϩ classic monocytes primarily act as scavengers, aiding in the neutralization of unbound LPS (65,86) and removal of apoptotic cells as part of the mononuclear phagocyte system (46). At rest, a majority of the CD14 ϩ CD16 ϩ monocytes are not present in the peripheral circulation but reside in the marginal pool and are released into the peripheral circulation via catecholaminemediated sympathetic mechanisms (78).…”
Section: Discussionmentioning
confidence: 99%